Barriers to using antenatal care services in a rural district in Zimbabwe - Jesca Mutowo; Mariatha Yazbek; Annatjie van der Wath; Carin Maree (Elsevier, 2021)
Background: In Zimbabwe women still initiate antenatal care (ANC) after twelfth weeks of pregnancy. Few women return for repeat visits. Early and timely ANC ensure early detection and management of high-risk pregnancies. The study explored the barriers to use of ANC services by pregnant women to obtain baseline data for developing context specific initiatives to enhance ANC utilisation. Method: The qualitative study answered the question 'What are the barriers towards utilisation of maternal healthcare services?' Purposive sampling was used to recruit community members (men, chiefs, councillors and politicians), maternal healthcare providers (midwives, traditional birth attendants and village health workers) and postnatal women. After ethical approval was obtained, data was generated through focus group discussions using interviews. Thematic analysis was used to analyse the data. Findings: The four themes included barriers related to maternal healthcare providers, maternal healthcare users, social support systems and belief systems. Disrespect for maternal healthcare users, lack of resources at health facility, user insufficient knowledge, fear of HIV testing by both the user and partners, poverty, household responsibilities, lack of spousal support and involvement and failure to integrate traditional and religious knowledge in healthcare practices prevent women from utilizing ANC services in rural Zimbabwe. Conclusion: The study provides evidence that barriers to utilisation of ANC services are not solely rooted in the individual but are multifaceted covering maternal healthcare providers related barriers, support system related barriers, cultural related barriers and religious related barriers. A multisectoral approach to enhance utilisation of ANC services timely and regularly is recommended.